Modulation of Activity of Salivary Adrenomedullin by pH - Muhammad Behzad Salahuddin, Ehsan Rathore, Nasrullah Khan, Shahlisa Hameedi, Omair Anjum, Rubbab Zahra, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Adrenomedullin is a multi-factorial peptide secreted by a range of human cells and is found in high levels in saliva. One potential role of Adrenomedullin is the maintenance of oral health through its antimicrobial activity. Aim: To characterize how varying pH alters the antimicrobial effect of Adrenomedullin in short-term killing assays. Study design: Experimental, Laboratory-based study. Setting: Centre for Clinical and Diagnostic Sciences, Barts and The London, Queen Mary’s School of Medicine and Dentistry, Queen Mary, University of London. Method: Cultures of Escherichia coli and Staphylococcus aureus were used to demonstrate antimicrobial activity of Adrenomedullin at pH levels of 7.5, 6.5 and 5.5 by employing short-term bacterial killing assays. Result: The results showed differences in the antimicrobial activity of salivary Adrenomedullin at different pH levels against the two different bacterial species used but were not significant.Conclusion: The results concluded that while Adrenomedullin has an antimicrobial effect, a greater range of pH and inclusion of specific oral microbes in the study will be helpful in investigating the hypothesis. However, it is likely that changes in pH in the oral cavity are important for the antimicrobial activity of salivary Adrenomedullin. Keywords: Adrenomedullin (ADM), Minimum Inhibitory Concentration (MIC), Phosphate Buffered Saline (PBS)